Human respiratory syncytial virus and hospitalization in young children in Italy - Parvanè Kuhdari; Federica Brosio; Cristina Malaventura; Armando Stefanati; Andrea Orsi; Giancarlo Icardi; Giovanni Gabutti (BMC, 2018)
Abstract Background Human respiratory syncytial virus (hRSV) is ubiquitous and causes respiratory diseases in both children and adults. Worldwide, hRSV pneumonia is the second cause of postnatal infant death after malaria. Given the high impact in terms of morbidity, mortality and costs, especially in the pediatric population, hRSV is recognized as a global health problem and the WHO, in view of the availability of new vaccines, has urged an active surveillance program of virus-related infections. The aim of this study has been to evaluate the impact of hRSV infections in the Italian population, particularly the pediatric one, in terms of hospitalizations. Methods In the period 2001-2014, Hospital Discharge Records (HDRs) with the following diagnosis codes included in the primary diagnosis were evaluated: 466.11 (hRSV bronchiolitis), 480.1 (hRSV pneumonia) and 796 (hRSV). HDRs were supplied by the National Archive of HDRs data, Ministry of Health. Results During the period 2001-2014, 57,656 hospital admissions due to hRSV pathologies were performed. Most hospitalizations (88.8%) involved patients with less than 1 year of age. Considering only primary diagnosis, 93% of the admissions were due to bronchiolitis, 5% to pneumonia and 2% to not otherwise specified hRSV infections. In the period 2001-2014, the hospitalization rate in 0-2 years old children, was equal to 224.8, 9.6 and 4.6/100,000 for hRSV bronchiolitis, hRSV pneumonia and not otherwise specified hRSV infection, respectively. Conclusions This study confirms the high impact of hRSV on the pediatric population in the age class 0-4 years, with a peak in the first 12 months of life. Most hospitalizations were urgent, although the duration of the hospital stay was for the most part less than a week, with ordinary discharge at home. Pending the conclusion of ongoing clinical trials on different hRSV vaccine types, it is extremely important to have updated data on the impact of hRSV-related pathologies in the various age groups.